Technology Gap Matters on Spillover - Sawada, Naotaka (2012)
This paper develops an oligopoly model with endogenous technology spillovers through foreign direct investment (FDI). The foreign entrant brings a superior technology and therefore may spend resources to prevent spillovers of its technology to the home firm. The home firm has an incentive to spend resources to gain these spillovers. After firms strategically choose their expenditures to influence technology spillovers, they compete in a Cournot-Nash quantity game. This study provides theoretical insight on the positive and negative empirical spillover results of FDI on productivity of local firms. Up to a critical bound, the larger the initial technology gap between the foreign and home firms, the more the home firm spends to gain spillovers. Past that boundary, the home firm decreases spending. As a result, the home firm's profits from spillovers vary, but larger technology gaps engender greater net profit losses from FDI.